Intrinsic capacity, frailty, fall risk and environmental setting among older adults in India - Reddy, Shivananda V.; Ganna, Anil K.; Shivaprasad, Renta (International Journal Of Community Medicine And Public Health, 2026)
Background: Falls are a major cause of disability in India’s ageing population. The World Health Organization emphasizes maintaining intrinsic capacity (IC) and preventing frailty in older adults. However, urban–rural differences in these associations remain underexplored. This study examined the relationships among IC, frailty, and fall risk in older Indian adults, including urban–rural differences. Methods: We performed a cross-sectional analysis using Wave 1 (2017–2018) data from the Longitudinal Ageing Study in India (LASI), including 31,902 individuals aged ≥60 years. IC was measured using a composite score (0–10) across five WHO-ICOPE domains, and frailty was assessed using the Fried phenotype. Multivariable logistic regression accounts for complex survey design and covariates, estimated adjusted odds ratios (aORs) for falls, high IC, and frailty. Results: Fall prevalence was higher in rural areas (12.5%) than in urban areas (9.5%; p<0.001). Urban residence was associated with lower odds of falling (aOR 0.73; 95% CI 0.67–0.80) and higher odds of high IC (aOR 1.91; 95% CI 1.78–2.05). High IC was associated with lower odds of falling (aOR 0.80; 95% CI 0.67–0.96), while frailty increased fall risk (aOR 1.24; 95% CI 1.10–1.40). Depression and multimorbidity, which refers to the presence of multiple chronic health conditions, were associated with lower independence in daily activities (IC) and higher frailty. Conclusions: IC and frailty contribute to fall risk among older adults in India, with urban–rural differences suggesting an important role for environmental context.